Depiction of The Roles of Youth in The National Development in Selected Swahili Novel - Mwangi, Jackson Ndung'u (Machakos University Press, 2019)
The youths play a very important role in national development since they are very energetic, strong and forms the majority of the country’s population. Despite the fact that youths face a lot of challenges, they can also play a very important role in economic development and can bring a lot of changes in the society they live in for the benefit of all. This research aims at examining roles of the youths as an agents of positive change in their society in Swahili novel Kidagaa Kimemwozea which was written by Ken Walibora (2012) The nature of this research is descriptive and qualitive in nature and was based in the library. Tenets of Contemporary Realism Theory were used to analyze the outcomes of this research. The novel Kidagaa Kimemwoze a by Ken Walibora was used as a sample for this research and was arrived at through purposive sampling. It was observed that youths plays a very important role in bringing change in the society such as opposing a dictatorial leadership, dealing with corruption, changing people mindset on how to treat people with disabilities and opposing some oppressive traditions that hinders development in the society.
Keywords: Contemporary Realism; Youths; Agents of Change